Occupational Health Risks from Pesticide Exposure: Evidence from Thai Farmers - Pronrumpa Kanjanasingh; Thittaya Ngamsang; Preechaya Tajai (Natural and Life Sciences Communications, 2026)
Several pesticides are widely used in agriculture, yet many farmers lack adequate knowledge and protective practices, increasing risk of exposure and related health effects. This study aimed to screen health risks and analyze the factors affecting pesticide exposure among farmers in Chachoengsao Province, Thailand. Cross-sectional study was performed. Data were collected from 177 farmers who volunteered to participate. For pesticide exposure, 81.92% of farmers currently use pesticides, 57.25% sprayed pesticides themselves, 39.31% were present in the spraying area, and 3.45% were employed to spray for others. The average duration of pesticide exposure was 16.41 ± 13.37 years. A health risk assessment revealed that 33.79% of farmers were at high risk. Voluntary blood testing showed that 11.72% of exposed farmers had inhibited cholinesterase activity, indicating a potential health risk. Stepwise multiple regression indicated that wearing a mask or other respiratory protection while spraying pesticides had a statistically significant effect on cholinesterase activity (β = 374.569, P = 0.046), Forecasting the effect of pesticide exposure, wearing a mask could affect on cholinesterase activity for 3.6% (Adjusted R2 = 0.036, P < 0.05). This study suggesting that protecting against inhalation exposure substantially reduces the risk of pesticide absorption.